Pengaruh Kualitas Pelayanan dan Keragaman Menu Terhadap Keputusan Pembelian Di Café Socolatte Kabupaten Pidie Jaya - Zahara, Zahara Zahara; Agustinawati, Agustinawati Agustinawati; ., Siti Maimunah (Department of Management Faculty of Economics and Business, UNIVERSITAS MALIKUSSALEH, 2024)
The purpose of this study was to determine and analyze the effect of service quality (Physical Evidence, Reliability, Responsiveness, Assurance, Empathy) and menu diversity on purchasing decisions at Café Socolatte, Pidie Jaya Regency. The data analysis technique used is multiple linear regression analysis using the SPSS program. The results showed that simultaneously service quality and menu diversity had a positive and significant effect on purchasing decisions at Café Socolatte, Pidie Jaya Regency. Partially, service quality, physical evidence of reliability, responsiveness, assurance, empathy and menu diversity have a positive and significant effect on purchasing decisions at Café Socolatte, Pidie Jaya Regency. Keywords: Service Quality, Menu Diversity, Purchasing Decisions